Bioconversion of olive mill wastewater into high-added value products. (15th December 2016) - Dourou, Marianna; Kancelista, Anna; Juszczyk, Piotr; Sarris, Dimitris; Bellou, Stamatia; Triantaphyllidou, Irene-Eva; Rywinska, Anita; Papanikolaou, Seraphim; Aggelis, George
Abstract: Olive mill wastewater (OMW) contains a variety of assimilable carbon sources and therefore it can be regarded as fermentation medium for the production of high-added value products rather than as a waste material. In this study, OMW enriched with low cost carbon sources was used as culture medium for selected yeast strains cultivated in flasks and bioreactors. Lipomyces starkeyi NRRL Y- 11557 and Yarrowia lipolytica strains showed a noteworthy ability to accumulate lipids (15–25%, w/w) cultivated on OMW based media. Oleic acid was the major fatty acid in the lipids produced by the above mentioned yeasts followed by palmitic acid. On OMW media enriched with glycerol Y. lipolytica A6 strain produced also mannitol in considerable amounts (i.e. 13.4 g/L), while Y. lipolytica LGAM S (7) strain produced high quantities of citric acid (i.e. 30.3 g/L). Candida tropicalis LFMB 16 and Saccharomyces cerevisiae MAK-1, cultivated under non-aseptic conditions on OMW media enriched with glucose produced 21.9 and 31.3 g/L of ethanol, respectively. Remarkable phenolic removal was performed by strains of Y. lipolytica, C. tropicalis and S. cerevisiae, while color removal was only observed in trials performed with C. tropicalis and S. cerevisiae . The present study provides a new perspective for the production of high-added value metabolites having biotechnological interest from OMW based media along with OMW management. Highlights: OMW treatment and production of microbial metabolites by yeast strains was achieved. Non-aseptic conditions may be applied in low pH media. Phenolics and/or color removal by C. tropicalis, S. cerevisiae and Y. lipolytica was accomplished.